2019
DOI: 10.1177/2374373519879286
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Use of the After Visit Summary in a Primary Care Internal Medicine Practice

Abstract: Participants completed a cross-sectional survey about their use of the after visit summary (AVS) at a previous primary care visit. Of 355 participants, 294 (82.8%) recalled receiving it, 67.4% consulted it, 45.9% consulted it more than once, and 31.6% shared the AVS. In multivariable analysis, higher education and older age were associated with AVS consultation. Among the subset of 133 patients recalling personalized free-text instructions, 96% found them easy to understand and 94.4% found them useful. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The AVS has become an important tool for facilitating communication between patients and their providers. Although data on the utility of AVS in rheumatology clinics are lacking, one study from primary care suggested that 67.4% of patients consulted it, 45.9% consulted it more than once, and 31.6% shared the AVS 8 . However, numerous challenges exist to ensure that AVS' are patient-centered, modifiable, and nonburdensome for providers 9,10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVS has become an important tool for facilitating communication between patients and their providers. Although data on the utility of AVS in rheumatology clinics are lacking, one study from primary care suggested that 67.4% of patients consulted it, 45.9% consulted it more than once, and 31.6% shared the AVS 8 . However, numerous challenges exist to ensure that AVS' are patient-centered, modifiable, and nonburdensome for providers 9,10 .…”
Section: Resultsmentioning
confidence: 99%
“…Although data on the utility of AVS in rheumatology clinics are lacking, one study from primary care suggested that 67.4% of patients consulted it, 45.9% consulted it more than once, and 31.6% shared the AVS. 8 However, numerous challenges exist to ensure that AVS' are patient-centered, modifiable, and nonburdensome for providers. 9,10 Results from this quality improvement project help to understand features that would add to the patient-centeredness and providerfriendliness of an AVS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings from our study demonstrate that written communication can enhance a surrogate’s understanding of verbal communication. Currently, numerous clinical settings outside the ICU use clinical summaries to facilitate a patient’s understanding of his or her health, to encourage more active participation in medical decision-making, and to help limit issues related to patient recall (19, 20). Studies have shown that these tools are a valuable means of communication from both the patient and provider point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have reported personalized free-text instructions as helpful and easy to understand. 4 The Centers for Medicare and Medicaid Services (CMS) created financial incentives for healthcare organizations to improve the use of the AVS tool as part of the meaningful use requirement within the Affordable Care Act. 5 The requirement included providing patients with an AVS with relevant and actionable information and instructions after each office visit.…”
Section: Introductionmentioning
confidence: 99%